2013
DOI: 10.1016/j.jinteco.2013.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Robustness and exchange rate volatility

Abstract: Abstract. This paper studies exchange rate volatility within the context of the monetary model of exchange rates. We assume agents regard this model as merely a benchmark, or reference model, and attempt to construct forecasts that are robust to model misspecification. We show that revisions of robust forecasts are more volatile than revisions of nonrobust forecasts, and that empirically plausible concerns for model misspecification can easily explain observed exchange rate volatility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…To get the empirical evidence, we take logarithm of the raw data and detrend using the HP filter method. 9 Sales x t are from different sectors, and we take logrithm and detrend it to get HP filtered log(x t ). Table 2 gives the estimated persistence of sales using the whole sample as well as the before GFC sample.…”
Section: Data and Factsmentioning
confidence: 99%
See 2 more Smart Citations
“…To get the empirical evidence, we take logarithm of the raw data and detrend using the HP filter method. 9 Sales x t are from different sectors, and we take logrithm and detrend it to get HP filtered log(x t ). Table 2 gives the estimated persistence of sales using the whole sample as well as the before GFC sample.…”
Section: Data and Factsmentioning
confidence: 99%
“…augue that the DEP values between 0.1 and 0.3 are plausible. In the recent studies,Djeutem and Kasa (2013) show that to match the observed volatility of six U.S. dollar exchange rates (the Australian dollar, the Canadian dollar,…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Following Obstfeld (1994), we first consider a closed-economy equilibrium in which the two capital goods can be interchanged in one-to-one ratio and the amount of asset supply can always be adjusted to accommodate the equilibrium asset demand, (12). There are two types of equilibrium:…”
Section: Propositionmentioning
confidence: 99%
“…1 models and disengagement from risky investmentóput emphasis on agents' decisions for worstcase scenarios, which means that these activities involved model uncertainty and not merely an increase in risk exposure. This paper is also largely motivated by recent findings in the literature that introducing model uncertainty helps solve the excess volatility puzzle (Djeutem and Kasa 2013) and the current account volatility puzzle (Luo, Nie, and Young 2012). Also, the welfare costs due to model uncertainty can be significant.…”
Section: Introductionmentioning
confidence: 96%